The role of macrophages in renal fibrosis and therapeutic prospects - Di Niu; Jun Jie Yang; Dan Feng He (PeerJ)
Monocytes/macrophages are the key regulators of tissue repair, regeneration, and fibrosis. Monocyte-derived macrophages, which are characterized by high heterogeneity and plasticity, are recruited, activated, and polarized throughout the process of renal fibrosis in response to the local microenvironment. Increasing evidence suggests that phenotypic changes in macrophages are essential for chronic kidney disease (CKD) development and progression. Advanced bioinformatics and single-cell RNA sequencing analyses have revealed the critical mechanisms of macrophage iron homeostasis dysregulation and macrophage-to-myofibroblast transition (MMT), which may be a novel therapeutic target for renal fibrosis. In this review, we systematically examine the dynamic phenotype transitions of macrophages across distinct phases of kidney injury progression. Notably, we provide new insights into the multifaceted crosstalk between renal macrophages and neighboring parenchymal cells, including tubular epithelial cells, fibroblasts, podocytes, mesangial cells, and endothelial cells, mediated through diverse mechanisms, including soluble factors, extracellular vesicles, and direct cell-cell contact, and highlight the therapeutic potential of targeting macrophages.